Needs Analysis of Puberty Reproductive Health Literacy for Blind Students - Ajeng Galuh Wuryandari; Ruwayda Ruwayda; Nurmisih Nurmisih; Julaecha Julaecha (Asia Pacific Journal of Health Management)
Digital health is a discipline encompassing the study and application of digital technology to enhance health systems. It involves using digital health technology to benefit the general public, healthcare professionals, healthcare service providers, and the industry by empowering individuals and promoting a comprehensive health agenda. This uses a qualitative methodology, explicitly utilizing the phenomenological design. This study included a questionnaire analysis to assess the reproductive health needs of adolescents experiencing puberty. Additionally, we conducted in-depth interviews to collect data. School teachers, peers, and the use of online sites for information retrieval are the primary sources for providing reproductive health education to adolescent children. process encounters several challenges due to societal taboos and discomfort surrounding sensitive topics like sexuality. Consequently, children, including those with special needs and who require specialized approaches, often experience delays in acquiring knowledge about reproductive health. There is a pressing need for innovation in the healthcare sector to enhance the provision of digital services to various communities, including students.